Online Learning Model Implemented in Islamic Education in Post Covid-19 Pandemic: Case of Multicultural Students in Indonesia - Husni Idris; Rabiatul Adawiyah (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Limited studies focused on the teaching and learning process in the Covid-19 pandemic with multicultural conditions of students. Thus, this study aims to determine the various models of online learning in the field of Islamic education lessons (PAI) after the Covid-19 pandemic in Islamic high schools in East Kalimantan, Indonesia, in the context of multicultural conditions of students. This research is a case study where the focus of research is to investigate the natural phenomenon that happened during the Covid-19 pandemic especially related to how online learning was implemented in the teaching and learning process after the Covid-19 pandemic. The data collected focuses on gathering information about the actual conditions related to the various models of learning used by teachers in the field of Islamic education lessons. The data sources in this study consist of primary and secondary data sources gained from 26 teachers in 8 Islamic high schools in East Kalimantan, Indonesia. The results of the study showed that the online learning model for the field of Islamic education lessons implemented after Covid-19 is a blended learning model. It is supported by online learning media such as WhatsApp Group, Google Classroom, Zoom Meeting, YouTube, Google Meet, Madrasah e-learning, and Facebook which can ease the students with multicultural circumstances in acquiring lessons from teachers. Advantages and challenges faced by teachers and students are explored in this research, and novelty and pedagogical implications are offered for future studies.